PENGEMBANGAN MEDIA PEMBELAJARAN SEJARAH BERBASIS VISUALISASI SITUS KOTA LAMA TEGAL UNTUK MENINGKATKAN APRESIASI CAGAR BUDAYA SISWA SMA NEGERI 3 KOTA TEGAL TAHUN 2015/2016 - Mirzachaerulsyah, Edwin; Wasino, W.; Musadad, Akhmad Arif (Sebelas Maret University (UNS), 2017)
The purpose of this research is the development of the potential of the cultural heritage site of the old town of Tegal as a medium of learning history so that it can increase the motivation of learning history and enhance appreciation of the students. This media can also be guidelines for the protection and preservation of cultural heritage objects at the site of the old town of Tegal. Research method used is the method of research development or Research and Development adapted & modified Borg & Gall. With the instructional design model ADDIE (Analyze, Design, Development, Implementation, Evaluation) of Molenda. The subject of research as much as 22 students of Class XI Social Science Senior High School 3 Tegal as controls and classes of 30 students of Class XI XI Social Science Senior High School 3 Tegal as class experiments. Data collection techniques using question form and achievement test. Data analysis techniques using descriptive analysis and test t test. Based on the analysis of the effectiveness of the test, the results of the post test experimental classes (media developed) higher than the class of the control (conventional). Based on the T-test test earned t 2.1 > 1.88 = conclusion can be drawn then H0 is rejected, meaning both groups have an attitude of appreciation are not the same. There is a difference of attitude scale self-test results on post test experimental classes and controls that prove that media-based learning, visualization of the site of the old town of Tegal is effective to increase the apreasiasi of cultural heritage.